Describing settings of care in the last 100 days of life for cancer decedents: a population‐based descriptive study. (24th October 2022) - Hafid, Abe; Howard, Michelle; Webber, Colleen; Gayowsky, Ana; Scott, Mary; Jones, Aaron; Hsu, Amy T.; Tanuseputro, Peter; Downar, James; Conen, Katrin; Manuel, Doug; Isenberg, Sarina R.
Abstract: Background: Few studies have described the settings cancer decedents spend their end‐of‐life stage, with none considering homecare specifically. We describe the different settings of care experienced in the last 100 days of life by individuals with cancer and how settings of care change as they approached death. Methods: A retrospective cohort study from January 2013 to December 2017, of decedents whose primary cause of death was cancer, using linked population‐level health administrative datasets in Ontario, Canada. Results: Decedents 125, 755 were included in our cohort. The average age at death was 73, 46% were female, and 14% resided in rural regions. And 24% died of lung cancer, 7% breast, 7% colorectal, 7% pancreatic, 5% prostate, and 50% other cancers. In the last 100 days of life, decedents spent 25.9 days in institutions, 25.8 days receiving care in the community, and 48.3 days at home without any care. Individuals who died of lung and pancreatic cancers spent the most days at home without any care (52.1 and 52.6 days), while individuals who died of prostate and breast cancer spent the least days at home without any care (41.6 and 45.1 days). Regardless of cancer type, decedents spent fewer days at home and more days in institutions as they approached death, despite established patient preferences for an end‐of‐life experience at home. Conclusions: In the last 100 days of life, cancer decedents spent most of their time in either institutions or at home without any care. Improving homecare services during the end‐of‐life may provide people dying of cancer with a preferred dying experience. Abstract : A population‐based descriptive study using linked health administrative data in Ontario, Canada, described where patients dying of cancer spent their last 100 days of life. From 2013 to 2017, patients dying with cancer spent most of their time in either institutions (25.9 days) or at home without any care (48.3 days).